1991
DOI: 10.1080/10438599100000001
|View full text |Cite
|
Sign up to set email alerts
|

R&D, Patents, and Market Value Revisited: Is There A Second (Technological Opportunity) Factor?

Abstract: It is known that innovations in the market value of manufacturing firms and their R&D expenditures are related (Pakes 1985, Mairesse andSiu 1984). This could be due to shifts in the demand for the output of a particular firm, to shifts in the technological opportunities available to the firm, or to both. In this paper we use innovations in patenting activity as an additional piece of information about technological shifts in order to attempt to identify the relative importance of these two types of shocks. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(112 citation statements)
references
References 18 publications
4
104
0
4
Order By: Relevance
“…Such study result shows that an increase in study on investment for R&D will promote result of patent (Griliches et al, 1991) that conforms to past study result. In addition, marginal effect of the number of concentrations of R&D human resource in relation to patent application and patentability showed 0.0094 of positive (þ) effect, whereas marginal effect of the number of cooperation of R&D human resource has negative (À) effect, which evidences importance of the number concentration of R&D human resource.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Such study result shows that an increase in study on investment for R&D will promote result of patent (Griliches et al, 1991) that conforms to past study result. In addition, marginal effect of the number of concentrations of R&D human resource in relation to patent application and patentability showed 0.0094 of positive (þ) effect, whereas marginal effect of the number of cooperation of R&D human resource has negative (À) effect, which evidences importance of the number concentration of R&D human resource.…”
Section: Resultssupporting
confidence: 88%
“…Measurement was made after performance variables were divided into patents, which are a form of direct performance, and new product development, which is a form of indirect performance. Patents are perceived as data universally used for conducting a quantitative study related to the traits of R&D and performance, and actually a typical data that can represent innovation activities in all the areas, featuring long-term accumulation (Griliches et al, 1991;Pérez-Cano and Villén-Altamirano, 2013). Therefore, it is highly APJIE 12,1 justifiable to use patent information in analyzing the relationships between technology innovation and corporate performance.…”
Section: Introductionmentioning
confidence: 99%
“…With quarterly data, four is the common choice for the number of lags which adequately captures the medium-run dynamics in the data. 27 This corresponds to one lag at annual frequencies. The one year lag is also a preferable choice given the short size of the available sample.…”
Section: Empirical Results From the Varmentioning
confidence: 99%
“…and increasing after the second year following the occurance of the shock, reaching a peak of 0.5 percent in the sixth year following the occurance of the shock. 28 Hours in the R&D sector exhibit a small increase in response to the sectoral productivity shock, followed by a 27 For instance, see Christiano, Eichenbaum and Evans (2005), Altig, Christiano, Eichenbaum and Linde (2005) and Fisher (2006). 28 Notice that the initial small and statistically insigni…cant e¤ect of the R&D productivity shock on the output of the consumption-good sector is consistent with the structure of our economic model in which shocks speci…c to the R&D sector do not have a direct contemporaneous e¤ect on the consumption-good sector output.…”
Section: Empirical Results From the Varmentioning
confidence: 99%
“…The reason is that technological opportunity may raise the average product of R&D without raising its marginal product, and therefore technological opportunity may not increase R&D investment (Klevorick et al, 1995). Empirical studies have found mixed results for technological opportunities (Cohen et al, 1987;Griliches et al, 1991). Again, the relationship between opportunities and the type of R&D is an underresearched topic.…”
Section: Demand Technology Opportunity and Appropriabilitymentioning
confidence: 99%